2015
DOI: 10.1186/s12872-015-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and associated factors among heart failure patients on follow up at Jimma university specialized hospital, Ethiopia

Abstract: BackgroundMalnutrition and cachexia are serious consequences of numerous chronic diseases. Severe heart failure patients could be related with marked weight loss. Malnutrition is associated with poor prognosis among heart failure patients. Despite its implication, factors associated with malnutrition among heart failure patients in Africa and Ethiopia was not addressed. Hence, in this study we tried to determine factors associated with malnutrition among heart failure patients on follow up at Jimma University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“… 22 23 Serum ALB is used to access protein malnutrition without calorie malnutrition which did not affect the anthropometric measurements (eg, weight). 24 Malnutrition was found to be associated with worsening of symptoms and poor prognosis. Multiple European studies showed malnourished patients with HF are weaker and experience fatigue earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 23 Serum ALB is used to access protein malnutrition without calorie malnutrition which did not affect the anthropometric measurements (eg, weight). 24 Malnutrition was found to be associated with worsening of symptoms and poor prognosis. Multiple European studies showed malnourished patients with HF are weaker and experience fatigue earlier.…”
Section: Discussionmentioning
confidence: 99%
“… 25 26 HF with hypoalbuminaemia, the indicator of malnutrition, was found to be associated with higher New York Heart Association functional class, elevated serum blood urea nitrogen and C reactive protein (CRP). 24 It should be noted that, although hypoalbuminaemia might reflect poor nutritional status, ALB reduction in chronic inflammation is frequent. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Researches at AMARE and others also proved that malnutrition had greater influence on elderly patients with heart failure. 15 Applied at early stages, enteral nutrition energy metabolism regulation therapy could considerably improve patients’ life quality. 16 Also, the time period of enteral nutrition therapy was closely related to the improvement of patients’ nutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-nine percent of the patients had malnutrition based on weight for height measurements. According to a report of heart failure patients in adults by Amare et al from Jimma University, in South-West Ethiopia, 77.8% of the these patients were malnourished [33]. It has been reported that the risk of death associated with heart failure is significantly increased in patients at risk of malnutrition or with concomitant malnutrition [34].…”
Section: Discussionmentioning
confidence: 99%